Immunization With a Secreted Esterase Protects Mice Against Multiple Serotypes (M1, M3, and M28) of Group A Streptococcus - Zhang, Xiaolan; Wei, Deqin; Zhao, Yuan; Zhong, Zhaohua; Wang, Yue; Song, Yingli; Cai, Minghui; Zhang, Wenli; Zhao, Jizi; Lv, Chunmei; Zhu, Hui (Frontiers in Microbiology, 2020)
ABSTRACT Streptococcal secreted esterase (Sse) is a platelet-activating factor acetylhydrolase that is critical for Group A Streptococcus (GAS) skin invasion and innate immune evasion. There are two Sse variant complexes that share >98% identity within each complex but display about 37% variation between the complexes in amino acid sequences. Sse immunization protects mice against lethal infection and skin invasion in subcutaneous infection with the hypervirulent CovRS mutant strain, MGAS5005. However, it is not known whether Sse immunization provide significant protection against infection of GAS with functional CovRS and whether immunization with Sse of one variant complex provides protection against infection of GAS that produces Sse of another variant complex. This study was designed to address these questions. Mice were immunized with recombinant Sse of M1 GAS (SseM1) and challenged with MGAS5005 (serotype M1, CovS mutant, and Sse of variant complex I), MGAS315 (M3, CovS mutant, and Sse of variant complex I), MGAS2221 (M1, wild-type CovRS), and MGAS6180 (M28, wild-type CovRS, and Sse of variant complex II). SseM1 immunization significantly increased survival rates of mice in subcutaneous MGAS5005 and intraperitoneal MGAS6180 challenges and showed consistently higher or longer survival in the other challenges. Immunized mice had smaller skin lesion and higher neutrophil responses in subcutaneous infections and lower GAS burdens in spleen, liver, and kidney in most of the challenge experiments than control mice. SseM1 immunization enhanced proinflammatory responses. These data suggest that Sse immunization has a broad benefit against GAS infections that can vary in extent from strain to strain and that the benefit may be due to the immunization-enhanced proinflammatory responses. In particular, immunization with SseM1 can provide protection against M28 GAS infection even though its Sse and SseM1 have significant variations.